The Role of GeoHealth in Science During Crisis. Issue 7 (1st July 2019) - Colwell, Rita R.; Machlis, Gary E.
Abstract: The likelihood that crisis events will increase in number and severity is significant. Science has served, and will continue to serve, to address crisis events, whether natural or human attributed. Science during crisis has distinctive requirements. A call to action for science during crisis has been made, and described here are recommendations for response by scientists, including those in disciplines associated with GeoHealth. Key Points: The interdisciplinary fields that comprise geohealth have a significant role in prediction, prevention, and recovery from disasters